2006
DOI: 10.1111/j.1600-9657.2006.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical effects of splint types on traumatized tooth: a photoelastic stress analysis

Abstract: This study was undertaken to assess the effect of splint type on stresses occurring around traumatized tooth by photoelastic stress analysis. Three semi-rigid splint types--a wire-composite splint, fiberglass splint and titanium trauma splint--were utilized for comparisons. Extracted left upper central and lateral incisors and the canine tooth of an otherwise healthy patient were embedded equidistantly in photoelastic resin. For all cases studied, a static axial and 20 degrees oblique force of 100 N was applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 28 publications
0
31
0
3
Order By: Relevance
“…All four QSs produced higher SpErels (QS1 PT: 32 To our knowledge, no 'gold standard' or official norm exists for splint rigidity classification. All four QSs produced higher SpErels (QS1 PT: 32 To our knowledge, no 'gold standard' or official norm exists for splint rigidity classification.…”
Section: Study Outcomementioning
confidence: 92%
See 1 more Smart Citation
“…All four QSs produced higher SpErels (QS1 PT: 32 To our knowledge, no 'gold standard' or official norm exists for splint rigidity classification. All four QSs produced higher SpErels (QS1 PT: 32 To our knowledge, no 'gold standard' or official norm exists for splint rigidity classification.…”
Section: Study Outcomementioning
confidence: 92%
“…Influence of splint type on splint rigidity (P-values) ruptured fiber apparatus and hematoma within the widened periodontal gap. Various different methods have been introduced for evaluating tooth mobility (3,(21)(22)(23)(24)(25)(26)(28)(29)(30)(31)(32). As a parameter for evaluating rigidity properties of dental trauma splints, the splint effect can be calculated as the difference of initial tooth mobility and mobility after splint insertion (3,10,(16)(17)(18).…”
Section: Methodological Factorsmentioning
confidence: 99%
“…Mandel and Viidik (12) demonstrated that the PDL achieved 70% of its original strength 14 days after extraction and replantation. Current literature has reinforced the importance of using a flexible splint to stabilize the teeth, allowing physiological movement of the traumatized teeth (7,(13)(14)(15). Based on all the available evidence, current treatment guidelines for traumatized permanent teeth recommend the use of a flexible splint, regardless of the type of trauma (16)(17)(18).…”
mentioning
confidence: 99%
“…Orthodontic wire and bracket splints, fibre splints and titanium trauma splints are also known as semi-rigid splinting techniques. 19,20 In the case presented, splinting of the tooth with an orthodontic wire and brackets was found to be very effective. Placement of a medium thick 0.016 x 0.022-inch stainless steel orthodontic wire in 0.018 x 0.025-inch slots of brackets and tubes provides ease of semi-rigid splinting.…”
Section: Discussionmentioning
confidence: 99%